Pinealectomy alters IFN-? and IL-10 levels in primary thymocyte culture of rats - Sahin, Zafer; Sandal, Suleyman; Yilmaz, Bayram; Bulmus, Ozgur; Ozdemir, Gokcen; Kutlu, Selim; Kelestimur, Haluk (C M B Assoc, 2018)
Melatonin, produced mainly by the pineal gland, has an immunomodulatory role. However, the effects of the pineal gland and/or melatonin on thymus cytokine levels such as interferon-gamma (IFN-gamma), interleukin (IL)-4, and IL-10 are not well known. Twenty-one male Wistar rats (220-250 gr) were randomly divided into three groups (n=7): intact control, sham, and pinealectomy. Primary thymocyte cultures were prepared from each group and dispensed into well plates as Control, DMSO (or vehicle), Sham-pinealectomy, Pinealectomy, Pinealectomy+10 mu M melatonin, and Pinealectomy+100 mu M melatonin. IFN-gamma, IL-4, and IL-10 concentrations were measured in the thymocytes (as nonstimulated and Concanavalin A-stimulated) after 24 h. IFN-gamma levels significantly increased and IL-10 levels significantly decreased in both media prepared from pinealectomized rats. There was no significant difference between the groups in terms of IL-4. In the pinealectomy+100 mu M melatonin group, IFN-gamma and IL-10 levels did not differ from the pinealectomy group. However, the dose of 100 mu M melatonin caused a decrease in levels of IFN-gamma in both thymocyte media and an increase in the concentration of IL-10 in Concanavalin A-stimulated thymocytes. In conclusion, pineal gland and or melatonin affect IFN-gamma and IL-10 levels in the thymus gland.
Keywords: Pineal gland; Melatonin; Cytokine; Thymocyte; T helper; Rat